Trikaya Foundation Partnership Pattern in the Development of Organic Rice Farming in Subak Purnajaya, Lebih Village, Gianyar Sub-District, Gianyar Regency - ANINDITA, ANAK AGUNG RISKHA; BUDIASA, I WAYAN; ANGGRENI, I G A A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019DO - 10.24843/JAA.2019.v08.i02.p04, 2019)
Trikaya Foundation Partnership Pattern in the Development of Organic Rice Farming in Subak Purnajaya, Lebih Village, Gianyar Sub-District, Gianyar Regency Rice as one of agriculture's mainstay commodities in Gianyar Regency whichhas big opportunity, but Subak Purnajaya in the Lebih Village only able to produce an average of 2.5 up to 3 tons/ha with conventional farming systems and do not get market guarantee. Seeing these conditions, the Trikaya Foundation created an organic rice pilot project by embracing farmers to be its partners. This study aims to: (1) Analyze the characteristics of Subak Purnajaya before the partnership is implemented; (2) Analyze the pattern and mechanism of partnership that is applied; (3) Analyze the obstacles faced in realizing the sustainability of partnerships between the foundation and subaks. The analytical method used was qualitative and quantitative descriptive analysis. The results of the study showed that (1) The characteristics of Subak Purnajaya before the partnership was implemented, namely the limited knowledge possessed by farmers and the subak was still applying conventional farming systems; (2) The partnership implemented in the Subak Purnajaya was a pattern of Agribusiness Operation Partnership; (3) The foundation constraints had not optimally accommodated farmers production and limited infrastructure facilities, while the constraints of farmers found it difficult to find harvesters during great harvest time and are still dependent on the foundation. Based on the results of the research, the foundation should be able to utilize the role of social media to reach a wider market segments and improve the management system in establishing partnerships, while farmers continue practicing organic farming because it is more profitable than the conventional systems.